Lesion Location Predicts Risk of Aspiration in Supratentorial Ischaemic Stroke (Faridpur Medical College Journal, 2020)
Stroke is defined as focal or global neurological deficit of non-traumatic vascular origin which lasts 24 hours or more if the patient survives. Many researchers showed that risk of aspiration after stroke has been related to brain stem lesions. Moreover, assessing the risk of aspiration pneumonia in supratentorial ischaemic stroke has been established in a few recent studies. Aims of study was to see the association of lesion location and of risk of aspiration pneumonia in supratentorial ischaemic stroke. The study was done by random sampling from hospital-based stroke patients. Out of these patients we collected data from 100 acute hemispheric infarct patients who got admitted in Dhaka Medical College Hospital from July 2013 to December 2013. Subcortical infarcts were associated with higher proportion of risk of aspiration on day 1 with relative risk 2.63 which was statistically significant (95 percent CI 1.43 - 4.86, pvalue 0.001). Extended risk of aspiration on day 7 was also found more in these patients (relative risk 8.29, 95 percent CI 1.96 - 35.09, p-value 0.0004). Moreover, risk of aspiration was found in 32 percent patients, of which 14 percent was proved to have extended risk at day 7. Subcortical infarction is associated with higher risk of aspiration pneumonia in supratentorial ischaemic stroke.Faridpur Med. Coll. J. Jul 2019;14(2): 79-81